707High levels of back disability, but not back pain, are associated with reduced physical activity in women. (2nd September 2021) - Alyousef, Bothaina; Kazemi, Zeinab; Cicuttini, Flavia; Heritier, Stephane; Wang, Yuanyuan; Urquhart, Donna
Abstract: Background: Although clinical guidelines recommend physical activity for low back pain (LBP), our understanding of the physical activity undertaken by people with LBP is limited. We examined the amounts, intensities and types of physical activity performed by community-based women with different levels of pain and disability. Methods: 542 women were invited to participate. Physical activity was measured using the International Physical Activity Questionnaire, and LBP and disability were assessed using the Chronic Pain Grade Questionnaire. Participants were categorised into no/low or high pain intensity and disability groups. Results: Women with high levels of back disability performed half the total physical activity of those with no/low levels of back disability (MET(hours/week): median(95%CI)=27.3(13.2-41.4) vs. 53.9(44.9-62.8), p=0.002), including less moderate (17.5(10.4-24.7) vs. 32.1(26.8-37.4), p<0.001) and domestic and gardening activity (14.4(7.2- 21.7) vs. 23.5(19.0-28.0), p = 0.02). Moreover, fewer women with high disability participated in vigorous (3(8.11%) vs. 134(32.0%), OR(95%CI)=0.17(0.04-0.75), p=0.02) and leisure activities (17(45.9%) vs. 294(70.2%), OR(95% CI)=0.44(0.21-0.94), p=0.03) compared to those with no/low disability. There were no differences in physical activity between women with no/low and high pain intensity (all p > 0.05). Conclusions: High levels of back disability, but not back pain intensity, were associated with reduced physical activity, including less total activity, moderate and vigorous intense activity, and discretionary activity. Key messages: These findings highlight the impact of high levels of disability on physical activity. Further work is needed to determine whether targeting these types and intensities of physical activity will help in reducing back disability.